2013
DOI: 10.1371/journal.pone.0072652
|View full text |Cite
|
Sign up to set email alerts
|

Association Study of Val66Met Polymorphism in Brain-Derived Neurotrophic Factor Gene with Clozapine-Induced Metabolic Syndrome: Preliminary Results

Abstract: The prevalence of the metabolic syndrome (MetS) is higher among patients receiving atypical antipsychotics (AAPs) treatment, and even among AAPs, treatment with clozapine has been shown to be associated with a higher long-term incidence rate of MetS. Likewise, brain-derived neurotrophic factor (BDNF) deficiency has been reported to result in metabolic traits, such as increased food intake, hyperphagia and obesity, etc. In this study, we hypothesized that a functional polymorphism (Val66Met) in the BDNF gene ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…However, fasting and postprandial plasma glucose were the only significant factors after adjusting for BMI. In another study [26], Val66Met polymorphism of BDNF gene (rs6265) was genotyped, and the serum levels of fasting glucose, triglyceride, and high density lipoprotein cholesterol were measured. There was a trend indicating a significant association between the homozygous Met/Met genotype and prevalence of metabolic syndrome in male patients (OR   2.39, 95% CI 1.05-5.41).…”
Section: Discussionmentioning
confidence: 99%
“…However, fasting and postprandial plasma glucose were the only significant factors after adjusting for BMI. In another study [26], Val66Met polymorphism of BDNF gene (rs6265) was genotyped, and the serum levels of fasting glucose, triglyceride, and high density lipoprotein cholesterol were measured. There was a trend indicating a significant association between the homozygous Met/Met genotype and prevalence of metabolic syndrome in male patients (OR   2.39, 95% CI 1.05-5.41).…”
Section: Discussionmentioning
confidence: 99%
“…For example, an association between the rs4074134- BDNF minor allele and diabetes mellitus type 2 were reported [26], and this variant was associated with BMI, waist circumference, fasting and postprandial plasma glucose, insulin and HOMA-IR in subjects without diabetes mellitus. In another study, the rs6265 variant showed a significant association between the homozygous Met/Met genotype and prevalence of metabolic syndrome in male patients [27]. …”
Section: Discussionmentioning
confidence: 99%
“…In schizophrenia, as in obesity, there is an imbalance between adiponectin and the proinflammatory cytokines TNF-α and IL-6 (70). Also, BDNF deficiency has been reported in increased food intake, hyperphagia and obesity (71). Obesity itself does not affect the value of BDNF in the serum in adults (72), but BDNF levels in plasma were decreased in patients with Metabolic Syndrome (MetS) compared with control subjects (73) (Figure 1D).…”
Section: The Role Of Bdnf and Cytokines In Schizophreniamentioning
confidence: 94%
“…Obesity itself does not affect the value of BDNF in the serum in adults (72), but BDNF levels in plasma were decreased in patients with Metabolic Syndrome (MetS) compared with control subjects (73) (Figure 1D). For the first time, Zhang et al (2013) tested the relationship between the BDNF Val66Met polymorphism and MetS in patients with schizophrenia under long-term clozapine treatment. BDNF serum levels appeared to be associated with clozapine-induced MetS, and that effect is only evident in male patients (71).…”
Section: The Role Of Bdnf and Cytokines In Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation